Design Optimization of Diaphragm Walls. (2015) - Ilieş, Nicoleta-Maria; Farcaş, Vasile-Stelian; Pop, Marius
Abstract: In the past years the diaphragm walls has become a constructive solution for the underground structures in the cities crowded areas. The design is one of the most complex stages in realizing the building and it is usually time consuming, therefore a parametric study indicating the differences between methods is an important tool for the designers. The purpose of the paper is to demonstrate how different calculation models influence the design and the main result is the comparison between the embedment depths, the values of bending moments and shear forces and the structure displacements for different diaphragm walls heights.